DEGREASING THE WHEELS OF FINANCE. (August 2014) - Berentsen, Aleksander; Huber, Samuel; Marchesiani, Alessandro
<x xml:space="preserve">Abstract</x> Can there be too much trading in financial markets? We construct a dynamic general equilibrium model, where agents face idiosyncratic liquidity shocks. A financial market allows agents to adjust their portfolio of liquid and illiquid assets in response to these shocks. The optimal policy is to restrict access to this market because portfolio choices exhibit a pecuniary externality: Agents do not take into account that by holding more of the liquid asset, they not only acquire additional insurance against these liquidity shocks, but also marginally increase the value of the liquid asset, which improves insurance for other market participants.